Efektifitas Penindakan Parkir Liar Pada Dinas Perhubungan Bidang Pengendalian Dan Operasional Dalam Mewujudkan Kelancaran Lalu Lintas Di Jalan Ahmad Yani Kota Bekasi - Purwantomo; Iwan Irwansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The effectiveness of illegal parking enforcement policies plays a vital role in managing orderly and smooth traffic, especially in densely populated urban areas such as Jalan Ahmad Yani, Bekasi City. The Department of Transportation, through its Division of Control and Operations, is responsible for enforcing parking regulations to ensure the fluidity of traffic flow. This study aims to analyze the effectiveness of the illegal parking enforcement program, identify the obstacles encountered, and examine the efforts undertaken to overcome these challenges. The research method employed is descriptive qualitative, using data collection techniques such as interviews, observations, and documentation. The theoretical framework is based on the effectiveness approach by Matini & Lubis, as cited in Husaini (2019), which includes the goal approach, system resource approach, and internal process approach. The findings indicate that the enforcement program has yielded fairly significant results but has not yet been fully effective. The obstacles identified include limited personnel and operational vehicles, low public awareness, and suboptimal utilization of technology. The efforts made include increasing patrol frequency, proposing additional resources, conducting public education, and planning the implementation of an electronic ticketing system (ETLE). In general, the illegal parking enforcement program has contributed to reducing violations; however, further improvements are needed in the areas of supervision, technology integration, and inter-agency coordination.